Facilitating collaborative design: a toolkit for integrating persuasive technologies in design activities - Jalowski, Max; Fritzsche, Albrecht; Möslein, Kathrin (Procedia CIRP, 2019)
Motivation and focus of the participants are important success factors in collaborative design processes. Persuasive technologies can be applied in such processes to increase the motivation of the participants. Combining three different perspectives discussed in current literature, this paper presents a toolkit to support the creation and integration of persuasive technologies in collaborative design. The toolkit contains a navigator that guides the user through the selection of suitable examples from a set of 25 application scenarios. These contain a general description of the scenario, at least one example from extant literature, and persuasive design principles that support the implementation in the user’s collaborative design process.<br
Keywords: Collaborative Design; Participatory Design; Persuasive Technology; Design Toolkit